Novel Architecture of Security Orchestration, Automation and Response in Internet of Blended Environment - Lee M; Jang-Jaccard J; Kwak J (Tech Science Press, 2022)
New technologies that take advantage of the emergence of massive Internet of Things (IoT) and a hyper-connected network environment have rapidly increased in recent years. These technologies are used in diverse environments, such as smart factories, digital healthcare, and smart grids, with increased security concerns. We intend to operate Security Orchestration, Automation and Response (SOAR) in various environments through new concept definitions as the need to detect and respond automatically to rapidly increasing security incidents without the intervention of security personnel has emerged. To facilitate the understanding of the security concern involved in this newly emerging area, we offer the definition of Internet of Blended Environment (IoBE) where various convergence environments are interconnected and the data analyzed in automation. We define Blended Threat (BT) as a security threat that exploits security vulnerabilities through various attack surfaces in the IoBE. We propose a novel SOAR-CUBE architecture to respond to security incidents with minimal human intervention by automating the BT response process. The Security Orchestration, Automation, and Response (SOAR) part of our architecture is used to link heterogeneous security technologies and the threat intelligence function that collects threat data and performs a correlation analysis of the data. SOAR is operated under Collaborative Units of Blended Environment (CUBE) which facilitates dynamic exchanges of data according to the environment applied to the IoBE by distributing and deploying security technologies for each BT type and dynamically combining them according to the cyber kill chain stage to minimize the damage and respond efficiently to BT.
Keywords: Blended threat (BT); collaborative units for blended environment (CUBE); internet of blended environment (IoBE); security orchestration, automation and response (SOAR)